2016
DOI: 10.1089/ther.2015.0035
|View full text |Cite
|
Sign up to set email alerts
|

Early Absent Pupillary Light Reflexes After Cardiac Arrest in Patients Treated with Therapeutic Hypothermia

Abstract: Loss of pupillary light reactivity is one recognized indicator of poor prognosis after cardiopulmonary resuscitation (CPR). However, drug overdose, low cardiac output, and/or resuscitation drugs can lead to impaired pupillary light reflex. To investigate pupillary light reflex status before therapeutic hypothermia (TH) in relation to neurological outcome, we retrospectively reviewed the data of a prospectively implemented TH protocol in patients with cardiac arrest (CA) at Mayo Clinic in Jacksonville, Florida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…2). However, in two small studies, FPR of this sign was 50% [62] at 24-48 h and 25% at 24-72 h [94]. In a multicentre study on 201 patients [95], one false-positive result was observed (FPR 2.6%).…”
Section: Evoked Potentials (Tables 17 18 19 20 21)mentioning
confidence: 91%
See 1 more Smart Citation
“…2). However, in two small studies, FPR of this sign was 50% [62] at 24-48 h and 25% at 24-72 h [94]. In a multicentre study on 201 patients [95], one false-positive result was observed (FPR 2.6%).…”
Section: Evoked Potentials (Tables 17 18 19 20 21)mentioning
confidence: 91%
“…This was documented from the very early phase (6-12 h) up to a median of 5 days after ROSC (Table 17). However, two studies reported a false positive rate of 50% [62] and 75% [94] for SSEP. In both of these studies, only a few patients were assessed with SSEP, which may have amplified the observed false positive rate.…”
Section: Short-latency Somatosensory-evoked Potentials (Sseps)mentioning
confidence: 99%
“…Pupil function abnormalities have been reported for a wide range of disorders, including alcoholism [ 49 , 50 ], mental health disorders such as seasonal affective disorders [ 51 ], schizophrenia [ 52 ] and generalised anxiety disorder [ 53 ], Alzheimer’s [ 54 , 55 , 56 ] and Parkinson’s [ 57 , 58 , 59 , 60 ] diseases, autism spectrum disorders [ 61 , 62 ], as well as glaucoma [ 14 , 63 , 64 , 65 ] and autonomic neuropathies associated with diabetes [ 66 , 67 , 68 , 69 , 70 ]. Additionally, pupillometry has been applied to other clinical fields, such as monitoring of central states in anaesthesiology and analgesia, as well as monitoring and prognosis following head injuries, cardiac arrest and drug overdose [ 71 ].…”
Section: Clinical Applications Of Pupillometrymentioning
confidence: 99%
“…The Glasgow coma scale motor score showed a strong predictive value for a poor outcome in non-sedated patients ( 20 ), but its diagnostic value has never been assessed in the early phase of CA ( 21 26 ). Loss of pupillary light reactivity is a recognised indicator of poor prognosis during and after cardiopulmonary resuscitation, even though it can be impaired in mild hypothermia, low cardiac output and modified by resuscitation drugs ( 21 ). Despite a high specificity for predicting a poor neurological outcome, its sensitivity is low ( 27 29 ).…”
Section: Discussionmentioning
confidence: 99%